Analisis Tipologi Sektor Ekonomi Potensial Kabupaten Kerinci Provinsi Jambi - Silvia Rahayu; Dorris Yadewani (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study aims to find out which sectors are the leading sectors in Kerinci Regency, to find out the growth rate of the leading sector GRDP and total GRDP and to find out the Typology of Each Economic Sector in Kerinci Regency. analyzed using the Location Quetiont (LQ), Growth Rate and Klassen Typology formula, with the following research results: I. The leading sectors in Kerinci Regency are, water pawnshops, waste and waste management, agriculture, forestry and fishery sectors, information and communication sector, other service sectors, government administration sector, health services sector and social activities, education services and real estate sector. 2. The growth rate in Kerinci Regency, especially in the number of Gross Regional Domestic Product of the leading sector, experienced an ups and downs or the absence of a balance in the growth rate as well as for the total Gross Regional Domestic Product at the growth rate, it also experienced an imbalance in the growth rate or experienced an ups and downs in the growth rate in Kerinci Regency 3. While the Klassen typology for The leading sectors in Kerinci Regency, namely the water supply sector, waste and waste management are in (Quadrant III) with information on advanced but depressed sectors, then for the Agriculture, Forestry and Fisheries, Government Administration, Real Estate, Health Services and social activities sectors, this sector is in (Quadrant II) with sectoral information that is potential or can still develop rapidly, for ( Quadrant I) there is the information and communication sector, other services and the last is education services with information on advanced and fast-growing sectors.